Enhancement of energy density for iron MOF-derived composite for aqueous supercapacitor by K3[Fe(CN)6] redox additive electrolyte - Bala Krishnan, Hanusha; Lim, Hong Ngee; Ibrahim, Izwaharyanie; Wahid, Mohd Haniff; Foo, Chuan Yi (Elsevier, 2024)
Redox additive added aqueous electrolyte attract extensive interest in supercapacitor application. Herein, the electrochemical of the synthesized Fe3O4/Si/GNP composite cathode electrode material was conducted in a two-electrode system via Swagelok cell assembly in the presence of with and without redox additive (0.2 M K3Fe(CN)6 in 1 M Li2SO4). The Fe3O4/Si/GNP composite was successfully synthesized by facile solvothermal method followed by calcination. The structural and morphology investigations of the Fe3O4/Si/GNP composite are conducted via XRD, FESEM, and BET analyses. The synergic effects between the composite material and redox-active ion (Fe2+/Fe3+) in the redox additive electrolyte enhance faradaic reactions, which are utilized to design a high-energy density supercapacitor. The Fe3O4/Si/GNP composite in redox additive electrolyte exhibits a 64.38 % increase in specific capacitance (319.45 F g−1 at 1 A g−1) and a 70.95 % increase in terms of energy density (35.56 Wh kg−1). Redox additive ions in the electrolyte enhance ionic conductivity and facilitate electron transfer across the porous structure of the Fe3O4/Si/GNP composite. The fast reversible kinetics of iron ions enable it to sustain decent cycle stability with a capacitance retention of 73.7 % after 1200 cycles.